Avaliação da multifuncionalidade e de custos de técnicas compensatórias de drenagem na revitalização de áreas urbanas em Guarulhos, SP - Oliveira, Alinne Prado de (2018)
Best management practices consist of technologies of low constructive complexity and low environmental impact, which aim to optimize the infiltration, detention and retention of rainwater, reducing runoff and high investments in hydraulic devices of traditional drainage. For these characteristics, they were used in landscape projects carried out in recent years in green areas in the city of Guarulhos - SP, with the purpose of solving the microdrainage of the projects, of valorizing the utilization of rainwater in the urban environment, as well as bringing improvements in the conditions environmental (soil, microclimate, greater diversity of flora and fauna species) of such areas. The objective of this work is to analyze the implementation of best management practices (BMPs) in 3 (three) projects of green areas of the municipality, from the point of view of hydrological functionality, urban insertion, implementation and maintenance costs, and user appropriation. Based on the PULS method - hydrological model of simulation - urban data collection of the surroundings, visits, photographic records of the place, elaboration of cost sheets and comparison with preexisting data, and interviews to the users of the places of study, results were obtained that demonstrated the potentialities and weaknesses of each BMP project implemented in public areas. In general, the evaluation showed that the BMPs have good acceptance by the user, mainly due to the urban insertion capacity of the projects carried out by the City Hall; that the implantation and maintenance costs of implanted BMPs were, on average, 16.25% lower than those of a possible conventional drainage implantation; and that the proper hydrological functioning of the structures has proved to be fundamental to the appropriation by the user. The work contributes, therefore, to the presentation of relevant aspects of the project of implantation of best management practices in public green areas of the cities, even in areas already consolidated, capable of promoting urban, environmental and, mainly, drainage improvements.